Understanding the mechanisms of dermal inhibitive and bioactive compounds from lactobacilli and bifidobacteria. - Liong , Min Tze (Universiti Sains Malaysia, 2013)

(untitled)
This project evaluated the production of bioactives that are essential for skin health from either lactobacilli or bifidobacteria. Lipoteichoic acid, peptidoglycan, hyaluronic acid, diacetyl, acid and neutral sphingomyelinase (SMase), were detected to be produced, and these compounds are important for the development of physical barriers in the stratum corneum. One of the stronger bioactive, phingomyelinase (SMase), was further optimized using magnesium sulphate (MgS04) and manganese sulphate (MnS04) via response surface methodology.